Full 2π tunable phase modulation using avoided crossing of resonances - Ju Young Kim; Juho Park; Gregory R. Holdman; Jacob T. Heiden; Shinho Kim; Victor W. Brar; Min Seok Jang (Nature Communications, 2022)
Though active metasurfaces have been attractive for applications requiring control of optical wavefronts, realizing metasurfaces with full phase control remains a challenge. Here, the authors report a metasurface design strategy for enhanced dynamic phase modulation and tunability.